2009
DOI: 10.1093/ndt/gfp515
|View full text |Cite
|
Sign up to set email alerts
|

A rare haplotype of the vitamin D receptor gene is protective against diabetic nephropathy

Abstract: Our study has identified a rare VDR haplotype that is protective against DN in patients with type 1 diabetes. Replication in a large, independent cohort is required to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…To date, there are 65 publications [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83] on the association of VDR gene SNPs in T1D: these include case-control datasets [20,22,23,25,26,27,28,…”
Section: Vitamin D Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are 65 publications [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83] on the association of VDR gene SNPs in T1D: these include case-control datasets [20,22,23,25,26,27,28,…”
Section: Vitamin D Pathwaysmentioning
confidence: 99%
“…A total of 39 publications support an association between VDR SNPs rs7975232 ( ApaI ), rs1544410 ( BsmI ), rs731236 ( TaqI ) and rs10735810 ( FokI ) alone or in combination with each other, (rs757343 Tru9I , rs1540339 and rs4760648) and T1D [19,21,22,23,24,26,27,28,29,30,34,35,36,37,38,40,41,42,43,44,46,48,49,50,52,53,55,56,59,60,61,62,63,65,68,69,70,71,73] (Table 2) in comparison with 16 studies that refute it [20,25,31,32,39,45,47,51,54,57,58,64,66,67,72,74]. …”
Section: Vitamin D Pathwaysmentioning
confidence: 99%
“…Among these, Bsm I, Apa I, Taq I, Fok I and Cdx2 are the most studied polymorphisms. It has been reported that these polymorphisms are associated with various diseases including psoriasis, diabetes mellitus and cancers [10,11,12,13,14,15,16]. Up to date, there is only one study showing that the Apa I polymorphism of the VDR gene is associated with vitiligo and might play a role in the etiopathogenesis of the disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…BsmI (rs1544410) polymorphisms in intron 8 of the VDR gene have been shown to be correlated with type 2 diabetes in Caucasian and some Asian populations (Oh and Barrett-Connor, 2002;Shi et al, 2007), but the ApaI (rs7975232) polymorphisms vary among races, and their association with diabetes is controversial (Dilmec et al, 2009;Ortlepp et al, 2003;Wang et al, 2003). Some reports have been present that the relationship between BsmI/ApaI polymorphisms and type 1 diabetic nephropathy or other chronic kidney diseases (Bućan et al, 2009;Martin et al, 2010;Mohammadnejad et al, 2011;Souze et al, 2007), So far, there is no sufficient evidence of association between BsmI, ApaI polymorphisms in VDR gene and type 2 diabetic nephropathy. In this study, we use PCR-restriction fragment length polymorphism (PCR-RFLP) to determine the BsmI, ApaI genotype and allele frequency of the VDR gene in patients with type 2 Contents lists available at SciVerse ScienceDirect Gene j o u r n a l h o m e p a g e : w w w .…”
Section: Introductionmentioning
confidence: 99%